STIM1 signaling modulates invasive phenotypic plasticity by regulating calpain-dependent cleavage of integrin-β4 in nasopharyngeal carcinoma cells - Weiming Deng; Wenlin Huang; Yujuan Huang; Lihong Huang; Linsong Ye; Fei Liu; Min Li; Jingjin Weng; Qian He; Jinyan Zhang; Shenhong Qu; Jiazhang Wei (Cancer Cell International)
Abstract Background Stromal interaction molecule 1 (STIM1)-mediated Ca2+ signaling modulates the malignant features of nasopharyngeal carcinoma (NPC), a unique Epstein-Barr virus (EBV)-associated human malignancy. Integrin-β4 is involved in EBV-promoted motility in NPC cells. However, the underlying mechanism through which STIM1 signaling manipulates the invasive characteristics of NPC cells and the implication of integrin-β4 remains elusive. The present study aimed to characterize the role of integrin-β4 in the phenotypic plasticity for the epithelial-mesenchymal and mesenchymal-epithelial transitions (EMT and MET), and determine whether STIM1 signaling enhances invasive potential by modulating integrin-β4 cleavage in NPC cells. Methods Western blotting of epithelial and mesenchymal markers, cell migration and colony formation assays were performed to evaluate the EGF-stimulated EMT and laminin-induced MET in vitro. A zebrafish xenograft model was employed to elucidate the proliferation of transplanted NPC cell spheroids in vivo. A tail vein injection-lung metastasis mouse model was utilized to determine the capacity for distant metastatic colonization of NPC cells. Immunohistochemical analysis was conducted to detect the expression level of integrin-β4 in NPC tissues. Results Integrin-β4 was required for the bi-directional epithelial-mesenchymal transition in NPC cells. Silencing of integrin-β4 inhibited cell migration and clonogenicity in vitro, reduced clonal expansion of tumor cell clusters in zebrafishes, and eliminated distant metastatic colonization in mice. STIM1 Ca2+ signaling modulated the redistribution of integrin-β4 in migrating NPC cells. Mechanistically, STIM1-mediated Ca2+ influx enhanced aggregation of integrin-β4 at the cell membranes by promoting the calpain-dependent cleavage of integrin-β4. Clinically, we confirmed that integrin-β4 was highly expressed in primary tumors and cervical lymph node metastases. Conclusion STIM1 signaling promotes invasiveness by enabling accelerated subcellular integrin-β4 redistribution, which is essential for maintaining the invasive plasticity of NPC cells.